Impact of materialism on purchase intention of sustainable luxury goods: An empirical study in India. Issue 1 (3rd August 2021) - Kaur, Jaspreet; Parida, Ratri; Ghosh, Sanjukta; Lavuri, Rambabu
Abstract : Purpose: This study aims to examine the impact of the three dimensions of materialism, namely, possessiveness, envy and non-generosity along with attitude on the purchase intention of sustainable luxury products. Design/methodology/approach: The research study contains a descriptive approach to research with a quantitative analysis done with exploratory and confirmatory factor analysis with 229 respondents. Findings: The findings of the results contribute to research by extending the model of the theory of planned behavior with the material dimensions as an add-on. Research limitations/implications: The same could have been extended to all major metro cities of Indian where luxury brands are present in malls. Practical implications: This shows that the consumer with a high level of materialism trait would be a very prospective segment for sustainable luxury brands. Originality/value: The study shows that the three dimensions of materialism do impact the purchase intention of sustainable luxury producers and these findings will be crucial for devising consumer behavior-based strategies for sustainable luxury brands.